2021
DOI: 10.1177/00208728211021144
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leisure-based community activities on neighbourhood support and the social cohesion of communities in Spain

Abstract: To analyse the effects of leisure-based community activities in improving neighbourhood support and social cohesion, data were collected in two neighbourhoods of Barcelona (Spain) through questionnaires and interviews. The results indicate that promoting neighbourhood support requires a different strategy from promoting participation in leisure-based activities aimed at developing social cohesion within a community. The study also suggests various useful strategies to strengthen the effects of leisure-based co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Sociocultural animation is an effective educational methodology for developing participation and citizenship in normalized sectors and situations of risk and social conflict. Its educational value is confirmed by its geographical diversity, sociocultural improvement effects, and its permanence in time, despite gaining various names like community development and dynamization (Morata & Palasí, 2012). The SEA is a set of actions by individuals, groups, or institutions promoting active participation in a community's social and cultural development within a specific territory (Trilla, 1997).…”
Section: Sociocultural Animationmentioning
confidence: 99%
“…Sociocultural animation is an effective educational methodology for developing participation and citizenship in normalized sectors and situations of risk and social conflict. Its educational value is confirmed by its geographical diversity, sociocultural improvement effects, and its permanence in time, despite gaining various names like community development and dynamization (Morata & Palasí, 2012). The SEA is a set of actions by individuals, groups, or institutions promoting active participation in a community's social and cultural development within a specific territory (Trilla, 1997).…”
Section: Sociocultural Animationmentioning
confidence: 99%
“…The former tends to be spatially more variable due to the dispersion of activity locations, making public transit often inefficient compared to private modes (such as cars) (Schlich et al, 2004). Despite being inefficient for the system, leisure travel generates health and well-being benefits (Fancourt et al, 2021;Sala et al, 2019) and social cohesion (Morata et al, 2021;Jennings and Bamkole, 2019). Recent literature on leisure travel has also shown that social connections strongly influence individual mobility.…”
Section: Leisure and Socially Motivated Travelmentioning
confidence: 99%
“…From the perspective of society, community leisure activities can promote community identity and thus, promote the harmonious and orderly development of society. Morata et al [ 21 ] confirmed that community leisure activities have a significant effect on improving community support and social cohesion.…”
Section: Literature Review Conceptual Framework and Hypothesesmentioning
confidence: 99%